HOW CAN ACCOUNTING BE INTEGRATED WITH ECONOMICS? - Smith, Caleb A. (The Accounting Review, 1952)
The accounting course for economics concentrators can and should integrate accounting concepts with those of economics. No attempt is made in this paper to consider the equally important problem of how integration with economics may be brought to accounting courses taught for concentrators in business administration, accounting and other subjects. If one turns to the authors of textbooks one gets little more help. Among the multitude of accounting textbooks while there are a few written from a management point of view there is none that attempts to integrate accounting with economics or even to present those aspects of accounting which are especially important from the point of view of economics. Before accounting and economics can be studied together, a knowledge of the rudiments of each must be acquired. The economics concentrator normally studies accounting after at least one semester of elementary economics. To supply a background in accounting, the accounting course must start with a brief training in bookkeeping technique.